Muslim cosmopolitanism in the Age of Empire - Alavi, Seema (Harvard University Press, 2015)
Muslim Cosmopolitanism in the Age of Empire recovers the stories of five Indian Muslim scholars who, in the aftermath of the uprising of 1857, were hunted by British authorities, fled their homes in India for such destinations as Cairo, Mecca, and Istanbul, and became active participants in a flourishing pan-Islamic intellectual network at the cusp of the British and Ottoman empires. Seema Alavi traces this network, born in the age of empire, which became the basis of a global Muslim sensibility--a form of political and cultural affiliation that competes with ideas of nationhood today as it did in the previous century. Alavi breaks new ground in the writing of nineteenth-century history by engaging equally with the South Asian and Ottoman worlds, and by telling a non-Eurocentric story of global modernity without overlooking the importance of the British Empire.